Early assessment of adolescents with suicidal ideation using diagnostic scales - Toapanta Yugcha, Iván Guillermo; Toapanta Paredes, Ximena Elizabeth; Defaz Cashabamba, Wendy Marilyn; Cortés Moya, Carolina Elizabeth (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Introduction: the evaluation of suicidal ideation in adolescents constitutes a fundamental component in the field of primary care, however, its approach can be difficult due to the limitations inherent to the level of communicative development typical of the youth stage.Objective: to determine, according to their importance, the usefulness of early evaluation scales for suicidal ideation in adolescents.Materials and Methods: a systematic review was carried out where 38 articles with the best level of evidence available were selected from databases such as Google Scholar, Scielo, Elsevier, Dialnet, Digital.csic, using the descriptors: evaluation, scales and suicidal ideation in adolescents, under inclusion and exclusion criteria.Results: the existence of risk factors associated with suicidal ideation in the adolescent population has been identified, where the family environment stands out; however, it is essential to take into consideration that adolescents can manifest warning signs, being the exaggeration of Emotions are one of the most notable indicators, which is why the various scales that show good to excellent reliability and validity values ​​should be applied, such as the DASS-21, Beck, ISO-30 and Plutchik Scales.Discussion: the scales show variable reliability and validity values, the DASS-21 scale has a reliability of ,93 and validity of ,95 in addition to an S:91 % and E:89 %, it is useful in identifying young people at risk of mental health problems, since it addresses the domains of depression, anxiety and stress, on the other hand, the Plutchik scale has a reliability of ,89 and validity of ,86, also with an S: 78 % and E: 79 %, used as form of screening in Ecuador, however, the ISO-30 scale with a reliability of ,84 and validity of ,80, and an S: 81 % and E: 82 %, is the only one that evaluates the five dimensions.Conclusions: it is recommended to use suicidal assessment scales in adolescents with solid reliability and validity, such as the DASS-21, ISO-30, Plutchik, Beck, in order to obtain an early assessment of the psychological state of adolescents at risk of suicide ideation.